Effect of bevel angle on microstructure and mechanical property of Al/steel butt joint using laser welding-brazing method. (15th January 2016) - Sun, Junhao; Yan, Qi; Li, Zhuguo; Huang, Jian
Abstract: Butt joining of AA6061 aluminum alloy and Q235 low-carbon steel of 2.5 mm thickness was conducted using laser welding-brazing method with ER4043 filler metal. An electro-galvanizing process of the steel was performed to obtain a zinc coating at the steel's bevel surface before welding. The brazing interface and the tensile strength of the joints were evaluated. The results showed that a sound butt joint between Al and steel was obtained, with the brazing interface consisted of zinc rich regions and a Fe–Al intermetallic (IMC) layer. The thickness and morphology of the IMC reaction layer were not constant but varied along the brazing interface. The morphology of the IMC reaction layer was more complex and the layer was thicker when a smaller bevel angle of the steel was used. All the joints fractured in the Fe2 Al5 layer of the brazing interface. The tensile strength of the joints was mainly determined by the bonding area of the brazing interface, and average tensile strengths of 110 MPa and 150 MPa were achieved when bevel angles of 45° and 30° were used respectively. Graphical abstract: Highlights: Fiber Laser welding-brazing was done to join Al/steel. Sound Al/steel butt joint was achieved. The bevel angle has a great effect on the brazing interface. The tensile strength was improved with larger bonding area. Maximum tensile strength of 174 was obtained for the butt joint.